A INFLUÊNCIA DA LEGISLAÇÃO URBANA NO USO DE VARANDAS EM EDIFÍCIOS RESIDENCIAIS MULTIFAMILIARES EM VITÓRIA - ES - Barros, Maria Cláudia de S. L. S. Brandão; Moça, Isabela Finochi Fernandes; Barros, Joana D'arc Pereira de; Maioli, Ricardo Nacari; Pagel, érica Coelho (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The balconies are architectural elements of great importance for the environmental comfort, mainly in warm and humid climate, whose premise is of shadowing and natural ventilation. However, this environment has been undergoing constructive changes over the decades. The objective of this study is to show how the multifamily vertical residential buildings of Praia do Canto, neighborhood in Vitória-ES, have changed their constructive typology in the area of balconies over the years, verifying if these modifications correlate with the legislative changes of the Urban Master Plans approved for this city. The methodology used was a bibliographic review, survey of approved projects in the local, and visits to the region. Analyzing the temporal evolution of the municipal legislations in the calculation of the Floor Space Index, it is concluded that after the first Master Plan there was an increase in the insertion of the balconies in the projects and footage, since the area of these environments was not computed in the Floor Space Index. And since 1995, with the new legislation (1995 e 2006), where the balconies areas have been counted, the balconies have been reduced, although it continues to be a resource explored by real estate market.